Evaluation of Lactose Level Intake and Whey Permeate Form on Nursery Pig Performance - Ethan B. Stas; Jason W. Frank; Tingting Wang; Joel M. DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 1,512 pigs (Line 337 × 1050 PIC; initially 10.4 lb) were used to evaluate lactose level and whey permeate form on nursery pig performance in a commercial environment. Pigs were weaned at approximately 19 d of age and were allotted to 1 of 4 dietary treatments arranged in a 2 × 2 factorial utilizing low or high lactose levels with either granular whey permeate (Dairylac 80, International Ingredients Corporation, Fenton, MO) or spray-dried whey permeate. There were 27 pigs per pen and 14 replications per treatment. Pigs were fed experimental diets in two phases with phase 1 having a 5 lb/pig feed budget and phase 2 having a 12 lb/pig feed budget. The low lactose diets consisted of 10.0 and 4.13% whey permeate for phases 1 and 2, respectively, and targeted a total lactose intake of 0.80 lb/pig. The high lactose diets consisted of 20.0 and 8.25% whey permeate for phases 1 and 2, respectively, and targeted a total lactose intake of 1.60 lb/pig. Following experimental diets, all pigs were fed a common corn-soybean meal-based diet until the completion of the study. There were no lactose level × whey permeate form interactions for the duration of the study (P>0.10). For main effects of lactose level, pigs fed high lactose levels had increased (P≤ 0.024) ADFI compared to pigs fed low lactose levels from d 7 to 21 and the experimental period (d 0 to 21). For main effects of whey permeate form, overall (d 0 to 42) pigs fed spray-dried whey permeate had improved (P= 0.041) feed efficiency compared to pigs fed granular whey permeate. There were no differences in mortality or removals between treatments (P>0.10). In conclusion, this study suggests a lactose intake of 1.60 lb/pig increases feed intake compared to a lactose intake of 0.80 lb/pig during the experimental period regardless of whey permeate form. Additionally, spray-dried whey permeate improved feed efficiency regardless of the lactose level fed.
Keywords: lactose; whey permeate; nursery pig